Bismuth as Smart Material and Its Application in the Ninth Principle of Sustainable Chemistry - Ayodele Temidayo Odularu (Journal of Chemistry)
This paper reports an overview of Green Chemistry and the concept of its twelve principles. This study focusses on the ninth principle of Green Chemistry, that is, catalysis. A report on catalysis, in line with its definition, background, classification, properties, and applications, is provided. The study also entails a green element called bismuth. Bismuth’s low toxicity and low cost have made researchers focus on its wide applications in catalysis. It exhibits smartness in all the catalytic activities with the highest catalytic performance among other metals.